2003
DOI: 10.1149/1.1619985
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Layered Li[sub 1−δ]Mn[sub x]Cr[sub 1−x]O[sub 2] by XANES and In Situ XRD Measurements

Abstract: A wide solid solution of lithium manganese chromium oxides, LiMn x Cr 1Ϫx O 2 (0 р x р 0.6), having the layered ␣-NaFeO 2 structure, was synthesized by employing the emulsion drying method, and the Mn and Cr oxidation states of the prepared powders were identified by combination of the Rietveld analysis of the X-ray diffraction ͑XRD͒ data and X-ray absorption near edge spectroscopic ͑XANES͒ analysis. A reversible structural change of LiMn 0.6 Cr 0.4 O 2 was observed using the in situ XRD technique after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…7(c) For LiCrO 2 , on the other hand, ν is found to be almost T -independent from 275 K to the highest T measured (475 K). This demonstrates that both µ + s and Li + ions are static in the LiCrO 2 lattice at least until 475 K. This is very consistent with the electrochemical behavior of LiCrO 2 [29,30]. Moreover, since E a for LiCrO 2 (19 meV) is very small compared with those for the other compounds (70 meV-115 meV), the small increase in ν with T for LiCrO 2 is likely caused by another mechanism, such as, an electron contribution.…”
Section: Linio 2 and Licro 2 [17]supporting
confidence: 82%
See 1 more Smart Citation
“…7(c) For LiCrO 2 , on the other hand, ν is found to be almost T -independent from 275 K to the highest T measured (475 K). This demonstrates that both µ + s and Li + ions are static in the LiCrO 2 lattice at least until 475 K. This is very consistent with the electrochemical behavior of LiCrO 2 [29,30]. Moreover, since E a for LiCrO 2 (19 meV) is very small compared with those for the other compounds (70 meV-115 meV), the small increase in ν with T for LiCrO 2 is likely caused by another mechanism, such as, an electron contribution.…”
Section: Linio 2 and Licro 2 [17]supporting
confidence: 82%
“…Furthermore, there is no information on the T dependence of a reaction surface of the Li x CoO 2 electrode in a liquid electrolyte. Therefore, we compare the µ + SR result only with the prediction at 300 K. Figure 6 shows the ZF-and longitudinal field (LF-) µ + SR spectrum for the Li 0.98 Ni 1.02 O 2 sample obtained at 300 K, 350 K, and 450 K, together with that for LiCrO 2 at 450 K. Here, LiCrO 2 poses the same R3m crystal structure as LiNiO 2 , but is electrochemically inactive [29,30], i.e. Li + ions are not deintercalated from the lattice by a usual electrochemical reaction.…”
Section: X Coo 2 [16]mentioning
confidence: 99%
“…These results would reflect the dissolution of hexavalent Cr from the formed passive layer. Myung et al [27] proved that trivalent Cr could be oxidized to hexavalent Cr at such a higher potential, as confirmed by X-ray absorption spectroscopy. As analyzed by ToF-SIMS in Fig.…”
Section: Chromiummentioning
confidence: 90%
“…[69][70][71] When the ionic liquid electrolyte NaFSA-KFSA (FSA represents the anion bis(fl uorosulfonyl)amide) was adopted as a thermally stable electrolyte, the NaCrO 2 electrode exhibited a stable discharge capacity of 113 mA h g −1 at a current density of 125 mA h g −1 and 90 °C with a 98.5% capacity retention. [ 69 ] A recent report by Yu et al showed that carbon-coated NaCrO 2 exhibits excellent capacity retention over 50 cycles with a reversible capacity of 120 mA h g −1 at a current density of 20 mA g −1 .…”
Section: O3-type Tmosmentioning
confidence: 99%